The Effect of Playing Online Games on the Fifth-Grade Primary Students’ Learning Outcomes - Kesia Simatupang, Ruth; Janson Silaban, Patri; Mahulae, Saut; Sipayung, Regina; Lumban Gaol, Rumiris (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
The present study discusses whether there is an effect of online games on the learning outcomes of class V students at UPT SD Negeri 064025 Flamboyan Raya Medan in the academic year 2022/2023 or not. The population involves 158 class V students at UPT SD Negeri 064025 Flamboyan Raya Medan. The sampling technique uses purposive sampling, which was totaled 28 students at class V-D of UPT SD Negeri 064025 at the academic year 2022/2023. The method used in this research is a quantitative survey with the research method type. The survey type of quantitative research method used in this research is to find the effect of playing online games on the learning outcomes of class V students at UPT SD Negeri 064025 Flamboyan Raya Medan. Based on the results of statistical processing, it shows that the level of addiction to playing online games among students is categorized as strong category with an average of 88.28. Meanwhile, student learning outcomes have not met the KKM that has been implemented with an average of 72.85. By using the test, tcount is 4,530 while ttable is 2,056, because tcount ≥ ttable. Then, Ho is rejected and Ha is accepted. This proves that there is a significant effect between playing online games on the learning outcomes of class V students at UPT SD Negeri 064025 Medan Selayang in the academic year 2022/2023.